Experiential Marketing Strategy In The Boarding School Education Ecosystem As An Effort To Increase The Loyalty Of Student Guardians At Islamic Boarding Schools - Maulidatul Adzimah; Muthi’ah Rahman; Annisa Tri Ananda Dewi; Moh. Mohlas; Ahmad Rausyan Fikri; Mohammad Abdul Aziz Al wahedi; Abdullah (Al-Qalam Institute, 2024)
This study aims to explore the implementation of experiential marketing within the boarding school ecosystem and identify the key factors that enhance parental loyalty. Employing a qualitative case study approach, data were gathered through observations, in-depth interviews, and documentation, and subsequently analyzed using data reduction, presentation, and interpretive conclusion techniques. Findings indicate that experiential marketing is not formally structured but naturally embedded in students’ spiritual, social, and academic experiences. Critical success factors include firsthand student experiences, service quality, effective communication, adherence to religious values, and the positive institutional image conveyed through documentation. These elements contribute to heightened parental satisfaction, trust, engagement, and loyalty, often manifested through recommendations and continued enrollment. The study underscores that a comprehensive, experience-based marketing strategy grounded in religious and educational values is more effective for fostering long-term parental loyalty than traditional marketing approaches, offering a practical framework for boarding schools seeking sustainable relationship-building strategies while enhancing their reputation and perceived educational quality.